(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yunasfi, Susetya IE, Utomo B, Dalimunthe A, Samsuri, Zaitunah A. 2024. Fungal diversity associated with the decomposition of Avicennia marina leaf litter at various salinity levels. Biodiversitas 25: 792-800. The process of litter decomposition in mangrove ecosystem is influenced by both biological and environmental factors. Biological factors include organisms, such as worms, snails, bacteria, and fungi, while environmental factors are soil, water pH, salinity, and others. Therefore, this study aimed to determine the effect of salinity level and length of decomposition period, dominant fungi, as well as carbohydrate and protein levels in Avicennia marina leaf litter. In the experiment, litter bags containing 50 g of A. marina leaf litter were used and placed at salinity levels of <10 ppt, 11-20 ppt, and 21-30 ppt. The results showed that the highest decomposition rate i.e., 6.90/year, with length of time = 0.15 years was found in A. marina leaf litter at a salinity level of 21 ppt-30 ppt. At salinity levels of <10 and 10-20 ppt, the decomposition rate was 4.55 and 5.91, respectively, while the litter period in soil was 0.22 and 0.17 years. Furthermore, the residual leaf litter decomposed at salinity levels of <10 ppt, 11-20 ppt, and 21-30 ppt was 6.67 g, 4.57 g, and 4.36 g, respectively. The average value of the Shannon diversity Index for fungal species in A. marina leaf litter, which had experienced decomposition ranged from low to moderate. At salinity levels of <10 ppt, 10-20 ppt, and 20-30 ppt, the values obtained were 1.96, 1.86, and 1.95 respectively. The fungal species diversity index was greater than the control, 1.26. Based on the results, A. marina leaf litter placed at salinity level of <10 ppt had the highest carbohydrate and protein content of 12.10 and 9.12%, respectively, while the lowest protein content of 8.28% was recorded at salinity level of 20-30 ppt. This study showed that the longer the decomposition period at various levels of salinity, the higher the protein content in absolute terms.